2021
DOI: 10.4018/joeuc.20211101.oa9
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Motivation and Information Security Policy Compliance

Abstract: Many existing studies focus on the effect of external influence mechanisms (e.g., deterrence) impacting information security policy compliance (ISPC). This study explores the formation of ISPC from an autonomous motivation perspective, based on social exchange theory and self-determination theory. Data were gathered by conducting a survey of 261 employees, with hierarchical regression analysis being used to test our hypotheses.The results indicated the following: First, job satisfaction and personal responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…A research study published in the Journal of Organizational and End User Computing found that cybersecurity training not only improved employees' knowledge but also positively influenced their attitudes and behavior towards cybersecurity. This shift in mindset contributed to a more proactive approach to security, reducing the likelihood of risky behaviors and enhancing overall organizational security (Rhee et al, 2017).…”
Section: Impact Of Cybersecurity Awareness Trainingmentioning
confidence: 99%
“…A research study published in the Journal of Organizational and End User Computing found that cybersecurity training not only improved employees' knowledge but also positively influenced their attitudes and behavior towards cybersecurity. This shift in mindset contributed to a more proactive approach to security, reducing the likelihood of risky behaviors and enhancing overall organizational security (Rhee et al, 2017).…”
Section: Impact Of Cybersecurity Awareness Trainingmentioning
confidence: 99%
“…The online experimental platform accumulates students' learning behavior data before, during and after class, and provides intelligent analysis tools to facilitate teachers to supervise the whole teaching process in an all-round way. In addition, students should open the cloud classroom at an appropriate time after class, open the courseware uploaded by the teacher in my learning interface for review, complete the homework, consolidate the knowledge learned in this class, and check their mastery level through the examination, so as to achieve knowledge internalization and clear and solid memory [14].…”
Section: Review and Promotion Stage After Classmentioning
confidence: 99%
“…Students No. 1,3,6,8,10,11,12,14,15,17,18,19,20 were selected as a group (high group), with the best performance and an mean value of 89.7; Students No. 2,4,5,13,22,21,23,26,28,33,34,36,38 were selected as group 2 (middle group), with mean value of 75.5; Students No.…”
Section: Influence Of Mixed Oto Teaching Devices On Students With Dif...mentioning
confidence: 99%
“…Learning motivation is extremely potent. We can stimulate learners to continuously study hard to improve learning efficiency by constantly stimulating people's learning motivation and cultivating learners' good learning habits (Hong & Xu, 2021).…”
Section: Construction Of Mobile Game Model In Teaching and Education ...mentioning
confidence: 99%